Badania kliniczne i doświadczalne w chorobach serca, płuc i naczyń The prognostic value of endothelin-1 precursor in patients with advanced chronic heart failure - Nowak, Jolanta; Rozentryt, Piotr; Zębik, Tadeusz; Majkusiak, Anna; Uszok-Stenzel, Ewa; Buchta, Piotr; Skoczylas, Ilona; Spinczyk, Beata; Poloński, Lech; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2005)
Introduction: It was previously reported that in patients with chronic heart failure (CHF) the plasma level of the endothelin-1 precursor (BET-1) is increased and associated with poor prognosis. Aim: The aim of the study was to assess the role of BET-1 as a predictive marker of death or urgent transplantation in patients with CHF in 3-year observation. Material and methods: Fifty seven patients with systolic CHF (52 men and 5 women, mean age 46±7 years; New York Heart Association [NYHA] class: 19-class II, 28-class III, 10-class IV) were enrolled. Mean left ventricular ejection fraction in HF patients was 23±5%. The study endpoint was performed at 3-years. Patients were subsequently stratified into those who died (n=22), received a heart transplantation (n=16) or survived (n=19). The control group consisted of 18 healthy volunteers. Plasma levels of BET-1 were analyzed in both groups, whereas basic echocardiography, standard right heart pressure measurements, peak oxygen consumption were evaluated in the study group alone. Results: Patients with CHF showed a significantly higher BET-1 concentration (median 6.3 fmol/ml, upper quartile – 7.8, lower – 4.3), as compared with the control group (median – 3.9 fmol/ml, upper quartile – 4.5, lower 3.0, p=0.002). Patients with moderate and severe CHF (NYHA III and IV) had significantly greater BET-1 values than did those with NYHA II (p<0.05). BET-1 concentration correlated positively with uric acid and CRP and negatively with peak oxygen consumption. The multivariate analysis revealed that BET-1 was neither an independent predictor of 3-year mortality nor predictor of heart worsening in patients with CHF. For these end-points only mean pulmonary artery pressure and sodium level have both retained independent predictive power. Conclusions: Our findings suggest that plasma BET-1 may be useful in the evaluation of CHF severity, but is not related to survival within 3-years clinical observation.